Ijtihad dan Pengaruhnya terhadap Perkembangan Ketatanegaraan dalam Sejarah Islam - Zahratul Idami (Universitas Syiah Kuala, 2011)
ABSTRACT: Ijtihad as a legal source beside al-Quran and Sunnah is an effort to create the law on he religious problem that has not been mentioned particulary n the sources, but in progress, it causes the differences in practice of state leaders from the prophet and the era after the prophet. This research explores the influence of it on the practice of state in Islam history cousing th differences on each period or era. All practices done has a legal based both al-Quran and Sunnah although it is just general, because ijtihad is also done based on both legal sources. This research applies juridical historical approach by looking at the basis sources of it in al-Quran and Sunnah and also the progress of it from the prophet era and the following era in deciding the policies on state progressing problem. Ijtihad and Its Influence on the Development of State in Islam History